CLINICAL AND DIAGNOSTIC FEATURES OF EPILEPSY WITH ACCOMPANYING (INACTIVE) ORGANIC ENCEPHALOPATHY - S. A. Gromov; A. A. Kolyada; Y. N. Khrolenkov (Эпилепсия и пароксизмальные состояния, 2016)
Clinical, anamnestic and immunological features, type of interrelation between organic and neurophysiologic brain disorders as well as peculiarities of pharmacotherapy were investigated in 166 patients suffering from epilepsy (E) combined with organic encephalopathy (OE). The morbid state in E and OE patients was found to be manifested by syndrome complexes, with each of them dominating at a certain stage. E intencity was noticed to depend on the type of cerebral structural-morphological disorders. The evaluation criteria of the severity degree (diagnostic algorithm to assessment of condition) of E progressing in interconnection with OE were developed. Specificity of topographic interrelations of morphological and neurophysiological brain defects were found to influence epileptogenesis level. The conclusion is that maladaptive influence of OE on mechanisms of cerebral homeostasis compensation in E results in lowering of OE responsiveness to pharmacologic treatment and requires more intensive therapy.